Economic and self: philosophy and economic from the Mercantilists to Marx - Fischer, Norman (Westport, 1979)
This book examines the interconnections between philosophy and economics in the late eighteenth and nineteenth centuries, including the economic ideas of philosophers and the philosophical ideas of economists. For the most part, the philosophers and economists studied here wrote within a period of about a century-from the early synthesis of free-enterprise theory found in Quesnay and Smith in the latter half of the eighteenth century, through Kant and Hegel writing within the tradition of German idealism, to Marx attempting to synthesize both traditions in the latter half of the nineteenth century. Insofar as these thinkers form a historical tradition, it exists between and shades into mercantilism on the one side and late-nineteenth-century opposition to subjective value theory on the other. The philosophers and economists studied are tied conceptually by the way they relate questions of the self to problems of individual and holistic explanation in economics.
Keywords: Economics